2012
DOI: 10.1155/2012/918719
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Dual-Task Walking Deficits in People with Parkinson's Disease: Motor and Cognitive Contributions, Mechanisms, and Clinical Implications

Abstract: Gait impairments in Parkinson's disease (PD) are exacerbated under dual-task conditions requiring the simultaneous performance of cognitive or motor tasks. Dual-task walking deficits impact functional mobility, which often requires walking while performing concurrent tasks such as talking or carrying an object. The consequences of gait impairments in PD are significant and include increased disability, increased fall risk, and reduced quality of life. However, effective therapeutic interventions for dual-task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
316
0
17

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(350 citation statements)
references
References 148 publications
(221 reference statements)
17
316
0
17
Order By: Relevance
“…As for AD, dual-taskrelated gait changes in the clinical phase of PD is clinically relevant to detect patients at risk of falls. Also, some studies have shown that dual-task walking performance was associated with gait quality (Kelly et al 2012), freezing (Spildooren et al 2010), disease severity, and disability (Fuller et al 2013). Hollman et al 2011 andLord et al 2013 (pace, rhythm, phases, asymmetry, variability, andpostural control), and arm swing parameters inspired from Mirelman et al 2016 (amplitude, variability, and Dual-task-related gait changes: comparison between AD and PD at the clinical stage Even though the neuropathological origin of dual-task-related gait changes is different between the two diseases, the corresponding gait patterns display some similarities, particularly in the pace, rhythm, postural control, and variability domains of gait.…”
Section: Discussionmentioning
confidence: 99%
“…As for AD, dual-taskrelated gait changes in the clinical phase of PD is clinically relevant to detect patients at risk of falls. Also, some studies have shown that dual-task walking performance was associated with gait quality (Kelly et al 2012), freezing (Spildooren et al 2010), disease severity, and disability (Fuller et al 2013). Hollman et al 2011 andLord et al 2013 (pace, rhythm, phases, asymmetry, variability, andpostural control), and arm swing parameters inspired from Mirelman et al 2016 (amplitude, variability, and Dual-task-related gait changes: comparison between AD and PD at the clinical stage Even though the neuropathological origin of dual-task-related gait changes is different between the two diseases, the corresponding gait patterns display some similarities, particularly in the pace, rhythm, postural control, and variability domains of gait.…”
Section: Discussionmentioning
confidence: 99%
“…5 Some studies have demonstrated that PD patients have impaired equilibrium and gait in DT conditions when compared to age-matched controls. 7,8 The interference of DT on PD is frequently associated with reduced gait speed as well as step asymmetry, variability and length. 8 Increased step variability during DT is associated to reduced executive functioning.…”
Section: Sourcesmentioning
confidence: 99%
“…7,8 The interference of DT on PD is frequently associated with reduced gait speed as well as step asymmetry, variability and length. 8 Increased step variability during DT is associated to reduced executive functioning. 9 In PD patients, the automaticity promoted by basal ganglia is compromised and it becomes necessary to consciously control gait.…”
Section: Sourcesmentioning
confidence: 99%
See 2 more Smart Citations